Textbook Analysis of "Grow with English Book 1" - Aulia, Najla Nurul; Ambarwati, Evi Karlina (ELTALL: English Language Teaching, Applied Linguistic and Literature, 2023)
Textbooks play an important role in teaching and learning. Hence, textbooks are required to meet the standard. The purpose of this study is to find out whether the book "Grow with English book 1" is appropriate to be used as teaching material. Content analysis was conducted by using the standard criteria from Badan Standar Nasional Pendidikan or National Education Standards Agency as well as the criteria of Cunningsworth (1995)'s theory. It was found the book met all the criteria, i.e. material, language, material presentation, and graphical aspects. It can be concluded that the book is suitable to be used in English classroom at elementary school level.